Internationalizing higher education: critical collaborations across the curriculum - Rhiannon D Williams; Amy Lee (Springer, 2016)
"Higher education is facing unprecedented change as todayℓ́ℓs graduates need particular skills, awareness, and knowledge to successfully navigate a complex and interconnected world. Higher education institutions and practitioners are under pressure to be attentive to internationalization initiatives that support increasingly diverse student populations and foster the development of global citizenship competencies